DETERMINING ZONES OF NINE MARINE PROTECTED AREA IN SULAWESI TENGGARA PROVINCE - Desita Anggraeni; Christian N. N. Handayani; Dirga Daniel; Agus Wahyudi; Tarlan Subarno; Zulfikar Afandy; Dyah R D Darmawan; Fikri Firmansyah; Estradivar (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2017)
Southeast Sulawesi Province is part of Sunda Banda Seascape and occupies the area of Coral Triangle that has high biodiversity. One of the way to protect areas of high ecological value is by establishing a Marine Protected Area (MPA). According to Goverment Regulation No. 60/2007 section 17. The purpose of this study is to find potential areas to be recommended as core zones, utilization zones and sustainable fisheries zones or other zones. Marxan analysis is a tool used to identify potential sites for the placement of core zones and utilization zones. The target of conserving this location is to protect the habitat of coral reefs, seagrass and mangrove. The proportions of targets used in the Marxan scenario for all three habitats are 30%, 40% and 50%. Result of nine MPAs zonation analysis in Southeast Sulawesi recommendations such as: core zone of MPA Muna Barat is 8% and 13% and utilization zone is 12%; Core zone in MPA Bombana is 8.6% and 5.7% meanwhile the utilization zone of 4.6% and 7.5%; Core zone in MPA Kolaka is Kolaka 10% and 6% moreover utilization zone 7%; Core zone of MPA Central Buton is 3% and 2% while utilization zone 9%; Core zone of MPA South Buton while utilization zone of 6.4% and 6.2%; Core zone of MPA Muna is 10% and 7% besides, utilization zone 8,5% and 23%; Core zone MPA North Kolaka is 4% and 7% while utilization zone is 4% and 49%; core zone MPA Buton is 2.5% and 3% while the utilization zones are 2.5% and 2.6%. Keywords Sunda Banda Seascape, Marxan, coral triangle